Leukocyte activation by (1→3)-β-D glucans - Yoshiyuki Adachi; Mitsuhiro Okazaki; Naohito Ohno; Toshiro Yadomae (Mediators of Inflammation)
We studied the activities of several kinds of β-glucans, including sonifilan, grifolan, Sclerotinia sclerotiorum glucan, laminarin and zymosan, on macrophages. Preculture of macrophages with inactive β-glucans rendered the cells unresponsive to subsequent stimulation with grifolan, suggesting a specific pathway in the β-glucan structure. The importance of protein C and phosphorylation of mitogen-activated protein kinase was demonstrated in the activation with grifolan or zymosan. Immunoprecipitation of complement receptor (CR3), coprecipitated other proteins carrying phosphotyrosine residues in stimulation with grifolan. These data suggest that protein kinase C and tyrosine kinases are essential for signal transduction, and that CR3 might participate in the activation through interaction with other intracellular proteins.